On Gendered Technologies and Cyborg Writing. Issue 2 (3rd July 2014) - Muhr, Sara Louise; Rehn, Alf; Kerfoot, Deborah; Knights, David; Sabelis, Ida
<x xml:space="preserve">Abstract</x> Since Hélène Cixous introduced it in 1975, the notion of a specifically feminine writing — écriture féminine — has been discussed as a provocative and potentially disruptive form of representation that breaks with masculine and authoritarian modes thereof. However, in this paper we will discuss how the notion of écriture féminine may itself be at risk of getting trapped within the gender binary its progenitors tried to break free from. As a commentary on this, we suggest looking at the gendered nature of the research text from the perspective of the technologies with which they are produced, as the writer — when writing/publishing — is always already embedded in the technologies of the publishing machine, turning (academic) writing into something akin to cyborg writing. We further suggest that an understanding of the cyborg nature of writing can introduce a parallel mode of inquiry, which holds the potential to enrich écriture féminine and stand as a critique of too simplistic readings of the same.